ANALISIS KESALAHAN SISWA MADRASAH TSANAWIYAH ROUDLOTUL MUBTADIIN WONOREJO PASURUAN PADA MATERI TEKANAN - Agus Qowiyuddin; Erni Wijayati (Universitas Nahdlatul Ulama Pasuruan, 2023)
The purpose of this study was to analyze the mistakes made by students of Madrasah Tsanawiyah Roudlotul Mubtadiin regarding problems in the material pressure. The research was carried out by giving individual written tests (three essay questions) on the material pressure. This study used descriptive qualitative method. Six students of Madrasah Tsanawiyah Roudlotul Mubtadiin who studied stress material participated in this research. Data collection techniques were carried out using interview techniques and material analysis was carried out in the data reduction, presentation and conclusion steps. Based on data analysis and discussion, the following conclusions can be drawn: 1. The mistakes made by students when solving problems related to pressure material were conceptual errors in understanding the concept of pressure, and solid, liquid, and gas pressures, strategic errors in the form of errors in determining symbols, and arithmetic errors in the form of errors in performing arithmetic operations. 2. The reasons for student errors are a. conceptual error: students study less, pay less attention to the teacher's explanation and are afraid to ask questions if there is material that is still not understood. In this case, students misunderstood the concept. b. strategic mistakes: Students forget, don't care, lack of practice questions, lack of variety of practice questions, rush and limited time to solve problems. And 3. counting errors: students are not careful and enter the wrong numbers when counting, and complete assignments in a hurry.